2020
DOI: 10.1111/1751-7915.13568
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining of a fungal endophyte of Taxus yunnanensis (Chinese yew) leads to the discovery of a novel azaphilone polyketide, lijiquinone

Abstract: Genome mining of Ascomycete sp. F53 (F53), a fungal endophyte of the traditional Chinese medicinal plant Taxus yunnanensis (Chinese yew), revealed 35 putative specialized metabolite biosynthesis gene clusters, one of which encodes a rarely seen tandem polyketide synthase pathway with close homology to azaphilone biosynthesis pathways. A novel compound, lijiquinone 1, was subsequently isolated from F53 and structurally and functionally characterized. The m/z 385 [M + H + ] + compound, comprised of a cyclohexeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 68 publications
(92 reference statements)
0
15
0
Order By: Relevance
“…With the revolution of high-throughput genome sequencing and assembly, combined with the development of novel bioinformatics pipelines for identification of gene clusters, scientist noticed the unexplored potential for novel metabolites production are hidden in microbial genomes [ 95 , 147 , 149 , 150 , 151 , 152 ]. Genome mining for predicting and isolating natural products based on genetic information without experimental trials, has been inspired by the observation that each microbial strain contains the molecular potential to synthesize much more compounds than experimentally detected.…”
Section: Genome Miningmentioning
confidence: 99%
“…With the revolution of high-throughput genome sequencing and assembly, combined with the development of novel bioinformatics pipelines for identification of gene clusters, scientist noticed the unexplored potential for novel metabolites production are hidden in microbial genomes [ 95 , 147 , 149 , 150 , 151 , 152 ]. Genome mining for predicting and isolating natural products based on genetic information without experimental trials, has been inspired by the observation that each microbial strain contains the molecular potential to synthesize much more compounds than experimentally detected.…”
Section: Genome Miningmentioning
confidence: 99%
“…This fact is exemplified in a recent study in Microbial Biotechnology where the combination of genome mining and phylogenetics of core polyketide synthase domains led to the discovery of an uncharacterized 35 kb biosynthetic gene cluster (BGC) in a fungal endophyte isolated from a traditional Chinese medicine plant. Importantly, subsequent high‐resolution mass spectrometry and NMR spectroscopy analyses linked this BGC to the production of a novel anti‐ Candida antifungal polyketide, lijiquinone (Cain et al ., 2020). Unfortunately, the majority of the BGCs involved in natural product synthesis remain silent under standard laboratory culture conditions and there is a lack of knowledge on the regulatory mechanisms and environmental cues that activate cryptic BGCs (van Bergeijk et al ., 2020).…”
mentioning
confidence: 99%
“…In addition, it has also been reported that enzymatically controlled Knoevenagel reaction (Mpp7) could lead to the linear lactone whereas spontaneous condensation gave the angular one (14). Reduction of the furanone moiety of the linear tricyclic products may lead to the yellow pigments monascin (16) and ankaflavin (17) while its C4a(5) double bond can be oxidized by MrPigF ((or MppG) a FAD--dependent oxidoreductase) to afford the orange pigments rubropunctatin (18) and monascorubrin (19). These two orange pigments can also lead to the formation of the red pigments rubropunctamine (20) and monascorubramine ( 21) by a direct reaction with endogenous ammonia or amino--acids (Figure 2).…”
Section: O N a S C U S P A T H W A Ymentioning
confidence: 99%
“…The biosynthetic pathway of azaphilones involving an hrPKS--nrPKS action in tandem was primarily found in the Aspergillus genus and has been described in Aspergillus nidulans (16), Chaetomium globosum (17), Ascomycete sp. F53 (18), Aspergillus terreus (19) and Aspergillus niger ATCC 1015 (20).…”
Section: The Aspergillus Azaphilone Pathwaymentioning
confidence: 99%
See 1 more Smart Citation